Rancang Bangun Sensor Node untuk Monitoring Parameter Cuaca dan PM2.5 Menggunakan Arduino WiFi - Retno Tri Wahyuni; Abdur Rahman Haritsah; Heri Subagiyo; Edi Rahmanto (Politeknik Caltex Riau, 2021)
The node sensor for monitoring weather parameters and PM2.5 consists of weather parameter sensors, such as temperature, humidity, sun radiation intensity, rainfall, wind speed and wind direction. In addition, there are air quality parameters contains, namely pm2.5 sensors. Data processing and delivery is carried out by Arduino Uno WiFi which is a microcontroller device that has been integrated with ESP8226 which is a module to connect with WiFi networks. Sensor data is sent from Arduino to the data base server to be displayed on the website. The test results of each sensor compared to BMKG data showed small measurement error results for temperature and rainfall parameters with error percentages of 4.61% and 9.95% respectively. The results of measuring wind speed parameters have a considerable error of 30.03% caused by wind speed measurements carried out at different altitudes to BMKG sensors. Measurements of wind direction show different wind direction frequencies because they do not set the same reference point as the BMKG sensor at the time of the sensor laying. The PM2.5 measurement also showed a considerable measurement error result of 14.7% because the laying of the sensor was not conditioned with standards as in the BMKG sensor so that the particulate sample measured was not the same as the BMKG sensor. For measurement of sun radiation intensity and humidity each has shown a trend that is in accordance with environmental conditions. Data delivery testing also works well because all data stored on the server database is in the correct column on the data base and shows the same results compared to the sample data that the sensor reads manually.